Technical Politics - Kirkpatrick, Graeme (Bloomsbury Academic, 2012)
P‰In our rush for growth have we trusted too much to computers - and what bearing does this have on the current global economic meltdown?/P‰ P‰In I‰Technical Politics /I‰Graeme Kirkpatrick clarifies the place of technology in critical theory, offering a strategic conception of the politics of technology design. In Part One he presents a social -relational definition of technology, locating technology design and innovation in terms of their social and economic co-ordinates in contemporary capitalism. Technology is positioned as a specific social sub-field with its own internal rules and a distinctive, structural relationship with economic processes and social conflicts. In Part Two he identifies the political openings presented by this definition. Going beyond existing critical and constructionist theory, he examines the role of information technology in the contemporary economic crisis, offering a radical new perspective on the future of technology and how that future might be organized to serve human interests. /P‰ P‰/P‰ P‰The book investigates: /P‰ P‰*The relation of technology and politics in Marxist political theory and the limitations of the Marxist framework /P‰ P‰/P‰ P‰*A social-relational definition of technology and technological development /P‰ P‰*The role of information technology in the contemporary economic crisis /P‰ P‰*The lost dreams of the 1970s - what went wrong? /P‰ P‰*A strategic conception of digital technology design and how its design might be shaped in the future./P‰